Atos de concentração no setor de telecomunicações no Brasil: uma análise entre 2012 e 2023 - Tamanini, Gabriel Felipe (Universidade Federal de São Carlos, 2025)
This study aimed to analyze the acts of concentration that occurred in the Brazilian telecommunications sector between 2012 and 2023. In order to verify whether the acts were able to influence, to some extent, the configuration of the structure of such sector. Based on the literature review on acts of concentration and on the telecommunications sector, as well as with the exploratory analysis of the nineteen acts of concentration that occurred in the period of analysis, it was possible to identify that although the acts analyzed do not substantially change the oligopolistic characteristic of the sector, they provide a segmentation of branches of activity within the market, and the deverticalization of operations.
Concentration acts in the telecommunications sector in Brazil: an analysis between 2012 and 2023
Keywords: Fusões e Aquisições; Oligopólio; Telecomunicações; Mergers and acquisitions; Oligopoly; Telecommunications; CIENCIAS SOCIAIS APLICADAS::ECONOMIA